2018
DOI: 10.1007/s00705-018-3819-5
|View full text |Cite
|
Sign up to set email alerts
|

Using genomic analysis to identify tomato Tm-2 resistance-breaking mutations and their underlying evolutionary path in a new and emerging tobamovirus

Abstract: In September 2014, a new tobamovirus was discovered in Israel that was able to break Tm-2-mediated resistance in tomato that had lasted 55 years. The virus was isolated, and sequencing of its genome showed it to be tomato brown rugose fruit virus (ToBRFV), a new tobamovirus recently identified in Jordan. Previous studies on mutant viruses that cause resistance breaking, including Tm-2-mediated resistance, demonstrated that this phenotype had resulted from only a few mutations. Identification of important resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 91 publications
0
30
0
1
Order By: Relevance
“…Jaag and Nagy [ 108 ] showed that environmental and host factors could play an important role in viral RNA recombination, one of the major driving forces in RNA virus evolution [ 103 ]. A recent example of the emergence of a resistance-breaking virus that may have resulted from host-switching, is the description of a new resistance-breaking tobamovirus, an Israeli isolate of Tomato brown rugose fruit virus ( ToBRFV), that is able to overcome Tm-2 -mediated resistance in tomato [ 109 ].…”
Section: The Genetic Background Drives the Evolution Of Resistancementioning
confidence: 99%
“…Jaag and Nagy [ 108 ] showed that environmental and host factors could play an important role in viral RNA recombination, one of the major driving forces in RNA virus evolution [ 103 ]. A recent example of the emergence of a resistance-breaking virus that may have resulted from host-switching, is the description of a new resistance-breaking tobamovirus, an Israeli isolate of Tomato brown rugose fruit virus ( ToBRFV), that is able to overcome Tm-2 -mediated resistance in tomato [ 109 ].…”
Section: The Genetic Background Drives the Evolution Of Resistancementioning
confidence: 99%
“…A new tobamovirus infecting tomatoes and peppers is Tomato brown rugose fruit virus (ToBRFV), which was recently discovered in 2014-2015 in Jordan [5] and Israel [6]. ToBRFV is considered more virulent than other known tomato-infecting tobamoviruses, as it breaks the popular Tm-2 2 resistance gene which is present in many commercial tomato cultivars [6,7]. ToBRFV outbreaks in greenhouse tomatoes have been reported in countries around the world, including China [8] and Palestine [9] in Asia, Egypt in Africa [10], Germany [11], Greece [12], Italy [13]), Turkey [14] and the United Kingdom [15] in Europe, and Mexico [16,17], the United States [18,19] and Canada [20] in North America.…”
mentioning
confidence: 99%
“…There has been some discussion about the possible pathways leading to the emergence of this new virus. A comprehensive phylogenetic analysis and genomic comparison of different tobamoviruses by Maayan et al () concluded that a host‐shifting event (jumping) of the ToBRFV variant occurred with a relatively low mutation rate within a very short time. It is also thought that ToBRFV may have emerged as a result of recombination.…”
Section: Emergence and Symptoms Of Tobrfv In Tomato Productionmentioning
confidence: 99%
“…Most importantly, genomic sequencing of emerging resistance breakers has demonstrated that they can differ by 9-15% from known viruses, for instance, when making comparisons between ToMMV and TMV or ToMV, which may have resulted from the innate mutability of the tobamovirus RNA genome (Domingo & Holland, 1997). In contrast, phylogenetic analysis has shown that the genomic sequence of ToBRFV differs from either ToMV or TMV by 18% and suggests that it could have originated from a common ancestor of ToMV and TMV (Maayan et al, 2018). Salem et al (2016) confirmed the viral causal agent as ToBRFV when a single local lesion taken from an inoculated Nicotiana tabacum 'White Burley' reproduced mosaic symptoms on tomato plants cv.…”
Section: Physical and Molecular Properties Of Tobrfvmentioning
confidence: 99%